Morphological, genome-size and molecular analyses of Apostasia fogangica (Apostasioideae, Orchidaceae), a new species from China - Yin, Ya-Yi; Zhong, Ping-Sheng; Zhang, Guo-Qiang; Chen, Li-Jun; Zeng, Si-Jin; Li, Ming-He; Liu, Zhong-Jian (Phytotaxa, 2016)
After examining morphological, molecular and genome-size evidence, we describe and illustrate a new orchid species, Apostasia fogangica, from Guangdong, China. Morphological comparisons indicate that A. fogangica is similar to A. shenzhenica, although the habit, leaves, inflorescences and fruit shapes and sizes differ. Comparison of the genome sizes in Apostasioideae show that A. fogangica is 1C=0.952 pg, which is double the size of A. shenzhenica but close to that of A. wallichii. Molecular analyses from combined nuclear and plastid datasets (ITS, matK and trnL-F) indicate that A. fogangica is sister to A. nipponica plus A. shenzhenica. The morphological, genome-size and molecular evidence support the hypothesis that A. fogangica is a new species.